PENGARUH ENTREPRENEURSHIP EDUCATION TERHADAP FINANCIAL LITERACY PADA SISWA SMA AL AZIZ ISLAMIC BOARDING SCHOOL (SCHOOL OF LEADERS AND ENTREPRENEURS) - Ratna Meisa Dai; Nurillah Jamil Achmawati Novel (Departemen Ilmu Administrasi Bisnis, Fakultas Ilmu Sosial dan Ilmu Politik, UNPAD, 2021)
This study aims to determine the effect of entrepreneurship education on financial literacy in Al Aziz Islamic Boarding School (School of Leaders and Entrepreneurs) high school students. As an entrepreneurship-based school, SMA Al Aziz Islamic Boarding School (School Of Leader and Entrepreneur) . Entrepreneurship education is carrying out entrepreneurial behavior, or several elements that influence these intentions, such as entrepreneurial knowledge, desire for entrepreneurial activities, or feasibility. Educational institutions can build basic entrepreneurial skills to foster entrepreneurial intentions and financial literacy, which is a special form of knowledge about finances for students at Al Aziz Islamic Boarding School (School Of Leader and Entrepreneur). The research method used is the quantitative method used by distributing questionnaires involving 51 students of SMA Al Aziz Islamic Boarding School. Sampling is done by probability sampling. The data obtained were processed to be tested for the effect of the measured variables. Data analysis using simple regression analysis.. Based on the results of the study, it shows that there is a significant positive effect of the entrepreneurship education variable on financial literacy.Penelitian ini bertujuan untuk mengetahui pengaruh entrepreneurship education terhadap financial literacy pada siswa SMA Al Aziz Islamic Boarding School (School of Leaders and Entrepreneurs). Sebagai sekolah berbasis kewirausahaa, SMA Al Aziz Islamic Boarding School (School Of Leader and Entrepreneur). Entrepreneurship education yakni melakukan perilaku kewirausahaan, atau beberapa unsur yang mempengaruhi niat tersebut, seperti pengetahuan kewirausahaan, keinginan dari kegiatan kewirausahaan, atau kelayakannya. Lembaga pendidikan dapat membangun keterampilan dasar kewirausahaan untuk menumbuhkan niat berwirausaha dan Financial literacy yakni bentuk khusus dari pengetahuan tentang keuangan para siswa di SMA Al Aziz Islamic Boarding School (School Of Leader and Entrepreneur). Metode penelitian yang dilakukan yakni metode kuantitatif digunakan melalui penyebaran kuesioner yang melibatkan 51 siswa SMA Al Aziz Islamic Boarding School. Pengambilan sampel dilakukan secara probability sampling. Data yang diperoleh diolah untuk diuji pengaruh antara variabel yang diukur. Analisis data menggunakan analisis regresi sederhana. Berdasarkan hasil penelitian menunjukkan terdapat pengaruh positif secara signifikan variabel entrepreneurship education terhadap financial literacy.